2010
DOI: 10.1128/mcb.01174-09
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion of a DNA Repair Protein in the RNome World: Is This the Beginning of a New Era?

Abstract: 3Apurinic/apyrimidinic endonuclease 1 (APE1), an essential protein in mammals, is known to be involved in base excision DNA repair, acting as the major abasic endonuclease; the protein also functions as a redox coactivator of several transcription factors that regulate gene expression. Recent findings highlight a novel role for APE1 in RNA metabolism. The new findings are as follows: (i) APE1 interacts with rRNA and ribosome processing protein NPM1 within the nucleolus; (ii) APE1 interacts with proteins involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 45 publications
4
91
0
Order By: Relevance
“…APE1 is a multifunctional and essential factor in mammals that was identified about 20 years ago as the major AP-endonuclease in the BER pathway, as well as a redox coactivator of transcription factors (37,157). The recent observation that APE1 is able to bind and cleave RNA highlighted previously unsuspected roles for the protein (77,138). We found indeed that this protein associates with NPM1 in the nucleolus, where it may have a functional role as RNA cleansing factor.…”
Section: The Paradigmatic Example Of the Ape1/npm1 Interactionmentioning
confidence: 61%
See 3 more Smart Citations
“…APE1 is a multifunctional and essential factor in mammals that was identified about 20 years ago as the major AP-endonuclease in the BER pathway, as well as a redox coactivator of transcription factors (37,157). The recent observation that APE1 is able to bind and cleave RNA highlighted previously unsuspected roles for the protein (77,138). We found indeed that this protein associates with NPM1 in the nucleolus, where it may have a functional role as RNA cleansing factor.…”
Section: The Paradigmatic Example Of the Ape1/npm1 Interactionmentioning
confidence: 61%
“…Remarkably, this peculiar region also accounts for noncanonical activities that have been ascribed to APE1, including its role in RNA metabolism (42,89,116,138,148,149). Over the past two decades, knowledge of the biological functions, mechanisms of action, interactions, and regulation of the APE1 protein has increased exponentially.…”
Section: Fig 5 Schematic Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned findings demonstrated that APEl can recognize and cleave abasic RNA, affect cell growth through its involvement in rRNA control mechanism, play a role as a novel RNA cleansing enzyme, and affect gene expression through post-transcriptional mechanisms (Vascotto et al 2009 andTell et al 2010).…”
Section: Discovery Of Abasic Rna Incision Activity and Its Role In Rrmentioning
confidence: 99%